Effects of probiotics and encapsulated probiotics on enteric methane emission and nutrient digestibility in vitro. Issue 1 (June 2021) - Abdelbagi, M; Ridwan, R; Fidriyanto, R; Rohmatussolihat,; Nahrowi,; Jayanegara, A
Abstract: The objective of this study was to evaluate the effects of probiotics and encapsulated probiotics on enteric methane production and the in vitro nutrient digestibility in ruminants. The probiotics used were from the group of lactic acid bacteria (LAB). The experiments were conducted in three dietary treatments (control diet, probiotics addition, and encapsulated probiotics addition) and three replicates. Each replicate was performed at a different week. The experimental diets were incubated in the in vitro rumen fermentation system for 72 h. Parameters observed were pH, total gas production, methane production, total volatile fatty acids, NH3, and the in vitro dry and organic matter digestibility (IVDMD and IVOMD, respectively). Data were analyzed using variance analysis and continued with the Duncan multiple range test to compare among the different treatment means. Results showed both the probiotics and the encapsulated probiotics decreased (P<0.05) the methane production by 6.1 and 33.1% compared to the control diet, respectively. Furthermore, these probiotics and encapsulated probiotics increased (P<0.05) total gas production by 15.7 and 233% than that of control, respectively. The TFVAs, IVDMD, IVOMD, and NH3 values of the diet supplemented with probiotics were higher than the encapsulated probiotics (P<0.05). It can be concluded that both the probiotics and the encapsulated probiotics effectively mitigate the in vitro methane production while simultaneously enhancing the total gas production.